Educação, racionalidade e emancipação em Habermas: implicações e contribuições do agir comunicativo na cultura organizacional escolar - Braga, Océlio Jackson (2012)
This is a research about education and rationality, whose theoretical referential are the modernity are the contributions of thinkers from Frankfurt School and critical theory of communicative action of Jürgen Habermas. In a perspective subjective-instrumental reason, school reproduces in their practice the model of rationality of capitalist society with its contradictions to preparing learners, in most of their formation, not to transform it, but to meet the needs of the market work. So the school moves away from its purpose, which is to promote independence and social emancipation. Habermas proposes communicative rationality as a more ample model of rationality, because he considers any congregation of society as a consensual and intersubjective community, in which peoples have voice and each person has him moment, and all inner truth – received or produced – is a liable speech to review and critique and, in political context, cam promote social emancipation. In this perspective the school is considered a community intersubjective and consensual that can incorporate in their pedagogical practice a communicative action and act critically to promote intellectual freedom, the political maturity and the involvement of its agents with the transformation of society. The main question of research is know why the communicative rationality is a broader concept of rationality and to what extent the communicative rationality can contribute in organizational culture in school with emancipator educational practices. The objective of this research is investigate the rationality according to Habermas perspective thinking about the communicative action in organizational culture of school. The methodology is qualitative and the consisted in a literature search.